The Evolutionary Status of Early-type Galaxies in Abell 2390 - Fritz, A; Ziegler, B; Bower, R; Smail, I; Davies, R (2003)
We explore the evolution of the early-type galaxy population in the rich cluster Abell 2390 at z=0.23. For this purpose, we have obtained spectroscopic data of 51 elliptical and lenticular galaxies with MOSCA at the 3.5 m telescope on Calar Alto Observatory. As our investigation spans both a broad range in luminosity (-22.3